2022
DOI: 10.1089/whr.2021.0076
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Seeking Health Care and Postintervention Pain Outcomes in Foot and Ankle Orthopedic Patients

Abstract: Background: A significant portion of the adults suffer from foot and ankle pain. The sex differences that exist throughout health care, pain management, and orthopedics may further complicate treatment strategies. The purpose of this study was to determine if there were any differences in women and men in health care seeking behavior and symptom chronicity in a West Texas orthopedic population with foot and ankle conditions. Materials and Methods: Data from 137 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A greater proportion of females were tested for HbA1c in the ‘pre-lockdown level’ (pre-pandemic stage), and this is expected as previous studies have shown the tendency for females to visit hospitals more than their male counterparts ( Figure 2A ) [ 17 - 19 ]. Gender stratification of results revealed that during the lockdown period, more females attended the clinics than their male counterparts, with the highest frequency being in the 60-69-year-old female age group.…”
Section: Discussionmentioning
confidence: 71%
“…A greater proportion of females were tested for HbA1c in the ‘pre-lockdown level’ (pre-pandemic stage), and this is expected as previous studies have shown the tendency for females to visit hospitals more than their male counterparts ( Figure 2A ) [ 17 - 19 ]. Gender stratification of results revealed that during the lockdown period, more females attended the clinics than their male counterparts, with the highest frequency being in the 60-69-year-old female age group.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, girls reported slightly worse health than boys. This could be related to women's tendency to seek medical care more frequently than men, which might make it more likely for them to receive some health diagnosis (Petrie et al, 2022). In addition to this, Q-Sorters could have held different gender expectations for the male and female participants, impacting introspection scores.…”
Section: Bivariate Findingsmentioning
confidence: 99%